Benchmarking the ethics of internal auditors: A comparative analysis of private and public sector - Evangelia Pappa; John Filos (SPOUDAI - Journal of Economics and Business, 2019)
The main purpose of the paper is to benchmark the ethical behavior of internal auditors in Greece proposing a theoretical framework for 'ethics' based on principles and rules of professional conduct. Furthermore, the paper aims at comparing internal auditors' ethical behavior among the public and private sector, highlighting possible similarities and differences. The quantitative research approach was employed with the use of a well-structured questionnaire. A total of 138 internal auditors from private and public organization participated in this research. They each resolved nine ethical dilemmas based on real-life situations. The internal consistency reliability of the primary data was estimated through Kuder and Richardson formula 21 (KR-21). The results indicate that the majority of internal auditors pose a high level of ethical behavior and also public sector auditors are more compliant with the Code of Ethics than those of private one. Lastly, the divergent answers are not negligible and it is vital to interpret them in a proper sense and not identify them as unethical behavior.
Keywords: M42; L29; 330; Internal Auditors; Code of Ethics; Ethical Dilemmas; Public and Private Sector; Greece